Deep sedation and anaesthesia in complex gastrointestinal endoscopy: a joint position statement endorsed by the British Society of Gastroenterology (BSG), Joint Advisory Group (JAG) and Royal College of Anaesthetists (RCoA). Issue 2 (9th January 2019) - Sidhu, Reena; Turnbull, David; Newton, Mary; Thomas-Gibson, Siwan; Sanders, David S; Hebbar, Srisha; Haidry, Rehan J; Smith, Geoff; Webster, George
Abstract : In the UK, more than 2.5 million endoscopic procedures are carried out each year. Most are performed under conscious sedation with benzodiazepines and opioids administered by the endoscopist. However, in prolonged and complex procedures, this form of sedation may provide inadequate patient comfort or result in oversedation. As a result, this may have a negative impact on procedural success and patient outcome. In addition, there have been safety concerns on the high doses of benzodiazepines and opioids used particularly in prolonged and complex procedures such as endoscopic retrograde cholangiopancreatography. Diagnostic and therapeutic endoscopy has evolved rapidly over the past 5 years with advances in technical skills and equipment allowing interventions and procedural capabilities that are moving closer to minimally invasive endoscopic surgery. It is vital that safe and appropriate sedation practices follow the inevitable expansion of this portfolio to accommodate safe and high-quality clinical outcomes. This position statement outlines the current use of sedation in the UK and highlights the role for anaesthetist-led deep sedation practice with a focus on propofol sedation although the choice of sedative or anaesthetic agent is ultimately the choice of the anaesthetist. It outlines the indication for deep sedation and anaesthesia, patient selection and assessment and procedural details. It considers the setup for a deep sedation and anaesthesia list, including the equipment required, the environment, staffing and monitoring requirements. Considerations for different endoscopic procedures in both emergency and elective setting are also detailed. The role for training, audit, compliance and future developments are discussed.